Overview of the safety, efficiency, and potential mechanisms of finerenone for diabetic kidney diseases - Chen, Wenmin; Zheng, Lingqian; Wang, Jiali; Lin, Yongda; Zhou, Tianbiao (Frontiers in Endocrinology, 2023)
Diabetic kidney disease (DKD) is a common disorder with numerous severe clinical implications.Due to a high level of fibrosis and inflammation that contributes to renal and cardiovascular disease (CVD), existing treatments have not effectively mitigated residual risk for patients with DKD.Excess activation of mineralocorticoid receptors (MRs) plays a significant role in the progression of renal and CVD, mostly by stimulating fibrosis and inflammation. However, the application of traditional steroidal MR antagonists (MRAs) to DKD has been limited by adverse events. Finerenone (FIN), a third-generation non-steroidal selective MRA, has revealed anti-fibrotic and anti-inflammatory effects in pre-clinical studies. Current clinical trials, such as FIDELIO-DKD and FIGARO-DKD and their combined analysis FIDELITY, have elucidated that FIN reduces the kidney and CV composite outcomes and risk of hyperkalemia compared to traditional steroidal MRAs in patients with DKD. As a result, FIN should be regarded as one of the mainstays of treatment for patients with DKD. In this review, the safety, efficiency, and potential mechanisms of FIN treatment on the renal system in patients with DKD is reviewed.